Perubahan Mood saat Premenstrual Syndrome pada Remaja Putri - Maylar Gurning; Dirgantari Pademme (Idea Pengabdian Masyarakat, 2021)
Premenstrual syndrome (PMS) is a common cyclical disorder teenage girl, characterized by consistent physical and emotional symptoms. Symptoms are predictable and usually occur on a regular basis 7-10 days before menstruation and will disappear at the time of menstruation. The most common PMS symptoms experienced by women during premenstruation include feelings of irritability and anxiety when dealing with PMS, lack of energy or weakness and irritability. Therefore, providing education related to PMS can provide input and knowledge to young women during PMS. The method of implementing the service is by providing education and assistance to adolescents about mood changes that occur during the occurrence of Premenstrual syndrome (PMS), because providing education related to PMS can provide input and knowledge to young women during PMS.